Tetraclinis articulata (vahl) masters: An insight into its ethnobotany, phytochemistry, toxicity, biocide and therapeutic merits - Sohaib Khatib; Mansour Sobeh; Latifa Bouissane (Frontiers Media S.A., 2022)
Tetraclinis articulata (Vahl) Masters, commonly known as Sandarac tree and Araâr, is the only species representing the genus Tetraclinis Masters. The plant has been extensively used for medicinal, artistic, and ritual purposes since its first recorded use in 1800 B.C. Recently, a full range of ethnobotanical investigations has been undertaken to document the plant's empirical knowledge. They reported the use of different parts, such as leaves, stems, cones, bark, and roots, as part of folk healing practices to manage diabetes mellitus, hypertension, fever, stomach disorders, and diarrhea, among others. The phytochemical studies have identified at least 130 compounds from leaves, cones, resin, bark, and woods. These chemical constituents are categorized into phenolic acids, flavonoids and their derivatives, volatile compounds, phytosterols, and fatty acids, among others. Furthermore, they have strongly been correlated with the promising antimicrobial, antioxidant, neuroprotective, antiurolithiatic, anti-inflammatory, antidiabetic, and cytotoxic properties of the plant. Toxicological studies argued that the plant is quite safe and devoid of eventual toxicity; however, in-depth investigations are required to validate the safety of the plant. The remarkable antimicrobial and antioxidant potencies of various extracts from the plant against a wide range of foodborne pathogens support their possible use to increase the shelf life of foodstuffs in the food industry. Likewise, various plant-based extracts have been proven to exert substantial biocidal properties, making them potential alternatives to synthetic pesticides in agriculture. The present review provides an up-to-date comprehensive insight about the ethnobotanical uses of T. articulata, along with its phytochemistry and biological activities to furnish directions for further studies. We also discussed the biocidal potency of the plant and highlighted its usage to extend the shelf life of perishable foods.